Extranodal extension in head and neck squamous cell cancer: is there a role for further stratification?. Issue 5 (June 2021) - Tirelli, G.; Tofanelli, M.; Sacchet, E.; Bussani, R.; Shafiei, V.; Gatto, A.; Boscolo-Rizzo, P.; Gardenal, N.
Abstract: To investigate the prognostic significance of the stratification of extranodal extension (ENE) into ENE minor (ENEmi, up to 2 mm) and ENE major (ENEma, over 2 mm) in non-HPV-related squamous cell cancers of the head and neck, we retrospectively reviewed microscopic slides from neck dissection specimens of ENE-positive patients and subcategorised them into ENEmi and ENEma. We then compared the two groups in terms of overall survival (OS), disease-specific survival (DSS), and disease-free survival (DFS). Forty-four patients with pathologically positive necks had ENE in the histological report. Twenty-six had ENEmi and 18 ENEma. The three-year OS was 46% in the ENEmi group and 38.9% in the ENEma group. DSS and DFS were 80.8% and 80.8%, respectively, in the ENEmi group and 61.1% and 77.8%, respectively, in the ENEma group. None of the comparisons revealed any statistically significant difference. The results of our survival analysis seem to show a trend towards better survival rates in the ENEmi group, particularly regarding OS. Nonetheless, extension of the tumour outside the lymph node capsule by more than 2 mm was not found to be significantly associated with any of the explored survival outcomes.